What is transformed, resists, or is strengthened in physical education in school contexts? Analyzing the dispositional plasticity of a female migrant student - Forestier, Anthony; Sempé, Gaëlle; Combaz, Gilles (International Journal of Qualitative Studies in Education)
This article presents the socializing effects of PE, and more broadly school contexts, on the set of dispositions of a Somali migrant girl, recently arrived in France. Shaped from various agents of socialization and according to her gender, her social class, her religion and her migratory background, this portrait shows how PE allows, through individual variations, to (trans)form or reinforce her ways of being, acting and thinking at school. Based on an ethnographic survey carried out in a French secondary school, our findings highlight Sarah’s taste for PE and for sport, is gradually taking shape, thanks to the support of her teacher. Moreover, while dispositional transformations have been observed in her investment in PE thanks to the persistence of her docility, an inertia to change remains concerning the acquisition of fine motor skills. Also, in practice, a triple division of gender, migration and language still persists in class.
Keywords: Physical education; ethnography; immigration; school; socialization